PRINSIP KEPASTIAN HUKUM YANG BERKEMANFAATAN TERHADAP PENGGUNAAN METERAI ELEKTRONIK DALAM TRANSAKSI DIGITAL DI INDONESIA - Ratnaningsih; Siti Umiyatun Azizah; Bangkit Luhur Prio Wicaksono (Collegium Studiosum Journal, 2026)
Digital transformation has led to the implementation of innovations in stamp duty affixation systems, one of which is the application of barcode-based electronic stamps (e-stamps). This research aims to examine the legal certainty regarding the validity of agreements affixed with e-stamps by referring to the Civil Code (KUH Perdata) and the Law on Electronic Information and Transactions (UU ITE). Using a normative juridical research method, it was found that the use of e-stamps is legally valid as proof of duty payment on documents, even though it's not a condition for the validity of an agreement according to Article 1320 of the Civil Code. E-stamps positively contribute to strengthening the proof of digital agreements, including electronic transactions, accelerating administrative processes, and maintaining document integrity and authentication. However, their implementation still faces obstacles such as a lack of public literacy, limited access to technology, and inconsistent acceptance by several institutions. Therefore, clearer technical regulatory support, increased public understanding, and legal reforms are needed so that e-stamps can fully provide legal certainty in the practice of electronic transactions in Indonesia.